Keharmonisan Rumah Tangga dalam Pernikahan Perjodohan: (Studi Kasus di Desa Punggulrejo Kecamatan Rengel Tuban) - Zaenal Mahmudi; Awalluddin, Ach Nurhamid (HOKI : Journal of Islamic Family Law, 2023)
Arranged marriage is one of the cultures in an effort to achieve marriage. An arranged marriage is the first opportunity for two people to get to know each other. In Islam, arranged marriage is often translated as "khitba". This research uses a qualitative approach, where the method used is to collect data from interviews in accordance with planned interests. Field research is essentially to find specifically and the reality of what has happened in society. The results of the analysis show that household harmony in arranged marriages, if seen from the naked eye, can be said to be running like a husband and wife in general, but there is inequality in the implementation of rights and obligations from four categories of rights and obligations, namely the rights and obligations of external support, the rights and obligations of internal support. , hadlanah, and how couples deal with family problems that result in one party feeling burdened. Keywords: Arranged marriage; household harmony; Rights and obligations.